Exploring Linguistic and Psychological Barriers to English Speaking Proficiency: A Qualitative Analysis of - Abu Hamid Muhammad; Muflihah (CV. DYOQU PUBLISHING MANAGEMENT, 2026)
Background: English speaking proficiency remains a significant challenge for junior highschool students in non-native English contexts. Many learners encounter both linguistic andpsychological barriers that limit their ability to communicate effectively. Although speakingcompetence is essential for global communication and academic development, the underlyingfactors influencing students’ speaking performance in Indonesian classrooms remaininsufficiently examined.Aims: This study aims to identify the linguistic and psychological challenges that hinder juniorhigh school students’ English Speaking proficiency. In addition, it investigates how classroompractices influence student participation and speaking performance in English learningactivities.Methods: This research employed a qualitative descriptive design. Data were collected throughclassroom observations, semi-structured interviews with students and teachers, anddocumentation analysis. The participants were eighth-grade students at a junior high school inPurwokerto, Indonesia. The collected data were analyzed using thematic coding to identifyrecurring patterns related to speaking difficulties and classroom interaction.Results: The findings reveal that students’ speaking difficulties are primarily associated withlimited vocabulary, pronunciation problems, anxiety, and low self-confidence. These linguisticand psychological barriers reduce students’ willingness to participate in oral communication.The study also shows that teacher-centered instructional practices tend to limit opportunitiesfor student interaction, which further constrains speaking development. Conversely, the use ofinteractive classroom activities significantly increases students’ engagement and willingness tospeak.Conclusion: The study concludes that improving English speaking proficiency requiresaddressing both linguistic competence and students’ psychological readiness. Teachers shouldadopt communicative teaching approaches, provide constructive feedback, and foster asupportive classroom atmosphere. Increased opportunities for peer interaction and regularspeaking practice are essential for strengthening students’ confidence and participation inEnglish communication.